Transient equilibrium determination of dopamine D2/D3 receptor densities and affinities in brain - Phan, Jenny-Ann; Wong, Dean F.; Chang, Natalie H. S.; Kumakura, Yoshitaka; Bauer, William R.; Gjedde, Albert (Frontiers in Nuclear Medicine, 2022)
Long-term alteration of dopaminergic neurotransmission is known to modulate the D2/D3 receptor expression in the brain. The modulation can occur as a response to pathological processes or pharmacological intervention. The receptor density can be monitored by in vivo positron emission tomography (PET) of [C11] raclopride. To obtain accurate measurements of receptor-ligand interaction, it is essential to estimate binding parameters at true (if transient) equilibrium of bound and unbound ligand quantities. We designed this study as a comparison of two quantitative approaches to transient equilibrium, the TRansient EquilibriuM BoLus Estimation (TREMBLE) method and the Transient Equilibrium Model (TEM) method, to determine binding parameters at transient equilibrium with bolus injection of the radioligand. The data demonstrates that TREMBLE unlike TEM identified the time at which equilibrium existed. TREMBLE revealed that equilibrium prevailed at one or more times after bolus injection and identified differences of receptor density among regions such as putamen and caudate nucleus. We demonstrated that TREMBLE is a quantitative approach suitable for the study of pathophysiological conditions of certain types of neurotransmission the brain.